2017
DOI: 10.1590/1518-8345.1917.2926
|View full text |Cite|
|
Sign up to set email alerts
|

Non-pharmacological interventions to promote the sleep of patients after cardiac surgery: a systematic review

Abstract: Objective:to analyze evidence available in the literature concerning non-pharmacological interventions that are effective to treat altered sleep patterns among patients who underwent cardiac surgery. Method:systematic review conducted in the National Library of Medicine-National Institutes of Health, Cochrane Central Register of Controlled Trials, Latin American and Caribbean Health Sciences Literature, Scopus, Embase, Cumulative Index to Nursing and Allied Health Literature and PsycINFO databases, and also gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
30
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 39 publications
1
30
0
5
Order By: Relevance
“…Individualized educational intervention effectiveness on self-care for sleep is demonstrated in a randomized clinical trial conducted in Sweden (22) , as well as found in a systematic review on the efficacy of non-drug interventions for sleep improvement, which indicates that educational strategies have been used successfully (23) . In this perspective, the relevance of the existence of an educative resource, constructed and validated, that can be used in health education about sleep.…”
Section: Discussionmentioning
confidence: 78%
“…Individualized educational intervention effectiveness on self-care for sleep is demonstrated in a randomized clinical trial conducted in Sweden (22) , as well as found in a systematic review on the efficacy of non-drug interventions for sleep improvement, which indicates that educational strategies have been used successfully (23) . In this perspective, the relevance of the existence of an educative resource, constructed and validated, that can be used in health education about sleep.…”
Section: Discussionmentioning
confidence: 78%
“…A realização do banho no leito provocou redução na glicemia mediana de doentes oncológicos internados na UTI, e, com isso, sugere-se sua efetivação como medida não farmacológica complementar para o controle glicêmico desses doentes. A utilização de medidas não farmacológicas apresenta bons resultados sobre outros desfechos clínicos, ainda Development, v. 9, n. 8, e08985353, 2020 (CC BY 4.0) | ISSN 2525-3409 | DOI: http://dx.doi.org/10.33448/rsd-v9i8.5353 que combinadas à utilização de fármacos, como melhora do sono de pacientes submetidos à cirurgias cardíacas (Machado, Souza, Poveda, & Costa, 2017) e no manejo da dor (Mota & Cunha, 2014), inclusive no paciente oncológico (Rocha, et al, 2015).…”
Section: Discussionunclassified
“…The review found some evidence that the use of eye masks or earplugs may have favorable effects on sleep and the incidence of delirium in adults in the ICU setting [ 105 ] . A more recent systematic review found that earplugs, eye masks, relaxation training and white noise or music were associated with increased sleep quality, however high quality studies as assessed by the Jadad score were absent [ 106 ] . A recent randomized controlled trial found that perioperative psychological support increased the postoperative quality of sleep and quality of life in patients following esophagectomy [ 107 ] .…”
Section: Non-pharmacological Treatmentsmentioning
confidence: 99%